STRATEGI KOGNITIF YANG DIGUNAKAN OLEH MAHASISWA EFL DALAM MENULIS BERBASIS PROSES - Angella Novitaningrum (PPPM STIT MIFTAHUL MIDAD, 2023)
This study aimed to analyze cognitive strategies employed by EFL students in their process-based writing. It used descriptive qualitative method that carried out undergraduate students of TBI at STIT Miftahul Midad Lumajang as the subjects of the study. In order to collect the data, observation and semi-structured interview were conducted. The findings revealed that the students use several writing cognitive strategies. In planning stage, they use brainstorming, outlining, and setting goal in order to help them generate and organize their ideas. In composing stage, they use drafting process, focusing on the audience and using self-regulation strategies to help them write effectively and efficiently. Further, in reviewing stage, they use several cognitive strategies to help them improve the quality of their text by proofreading, revising and seeking feedback. In addition, cognitive strategies have been proposed as an effective tools in order to enhance EFL students’ writing performance.